Halal awareness among the orang asli community : Knowledge Transfer Program (KTP) in selected Orang Asli villages - Khadijah binti Othman (International Institute for Halal Research & Training, International Islamic University Malaysia, 2016)
Industrial Master Plan (IMP) 2006-2020 aims to make Malaysia the global halal hub for the production and trade of halal goods and services. More importantly, the positive outputs of the halal industry must reach all segments of people including the underserved community such as the Orang Asli community. Due to the increasing number of people within the Muslim Orang Asli community, halal matters have become one of the crucial aspects to be monitored. Besides, past research has identified that the community in urban areas are highly aware on halal consumption compared to the community that lives in rural areas. Therefore, the aims of this study are to study the level of halal awareness among the Orang Asli, identify the factors that contribute to their level of halal awareness and analyze the issues and challenges in enhancing halal awareness and education in this community. The methods involved document analyses, short term on-site observation and interviews. The Knowledge Transfer Program (KTP) report is the prime source in this study. The programme was conducted under the purview of the IIUM International Institute for Halal Research and Training (INHART) between March 2013 to December 2015 in five selected sites in the states of Pahang, Perak, Negeri Sembilan and Selangor. The findings of the study imply that the level of halal awareness amongst the Orang Asli community is minimal and understanding of halal is restricted to halal food consumption only. There are many factors contributing to their minimum level of halal awareness including inadequate religious commitment, different food culture, educational and geographical backgrounds, language barrier and contrast in pedagogy. In order to make Orang Asli community well-aware and be educated on halal issues, necessary steps must be taken during the early stages of childhood to ensure the chain of knowledge would be continuous and sustainable through generations.